Characterisation of phase distribution in a Peirce-Smith converter using water model experiments and numerical simulation - Chibwe, D.; Akdogan, G.; Aldrich, Chris; Taskinen, P. (Maney Publishing, 2011)
In this study, we have experimentally and numerically studied fluid flow behaviour in industrialPeirce–Smith converter (PSC) using cold model simulations. The two- and three-dimensionalsimulations of the three phase system were carried out using volume of fluid (VOF) and realisablek–e turbulence model to account for the multiphase and turbulence nature of the flow respectively.These models were implemented using commercial computational fluid dynamics (CFD) numerical code FLUENT. The cold model for physical simulations was a 1 : 5 horizontal cylindrical container made of Perspex with seven tuyeres on one side of the cylinder typifying a PSC. Compressed air was blown into the cylinder through the tuyeres simulating oxygen enriched air injection into PSC. Industrial treated feed, product and byproduct referred to as matte-white metal and slag were simulated with water and kerosene respectively in this study. The influence of blowing conditions on the distribution of phases was studied with five different compressed air volumetric flowrates at constant simulated matte and slag ratios. Both numerical and experimental simulations were able to predict the dispersion characteristics of the system in relation to flow and have substantially added to the understanding of the fluid dynamics of PSC.